The perspective of pedagogical innovation in the French higher education. - Zabolotska, Iryna; Заболотська, Ірина Олександрівна (Дніпровський державний аграрно-економічний університет, 2019)
Розглядається проблема розвитку, трансформацій та інновацій у педагогічній системі вищої освіти Франції за умов змін потреб та очікувань студентів у ХХІ столітті. The focus is on the problem of pedagogical development, innovation and transformation of the French higher educational system, with consideration of the changes in students’ needs and expectations in the XXI century.
Перспективи педагогічної інновації у вищій освіті Франції
Keywords: pedagogical innovation; педагогічна інновація; higher education; вища освіта; France; Франція; pedagogical transformations; педагогічні трасформації